Analysis of a Rooftop Solar Power Plant in the Amamapare Coal-Fired Power Plant Area to Maximize the Plant’s Energy Output - Oktapianus Ala; Jaka Windarta; Sri Widodo Agung Suedy (Jurnal IPTEK Bagi Masyarakat, 2026)
The increasing electricity demand in the operational area of PT Freeport Indonesia, particularly at the Amamapare Coal-Fired Power Plant, has encouraged the integration of renewable energy systems to reduce fossil fuel dependency and carbon emissions. This study aims to evaluate the technical, economic, and environmental feasibility of utilizing the coal stockpile roof area for a rooftop solar power plant installation. The research employed a quantitative descriptive approach using field observations, operational data, and PVsyst simulation. The results indicate that the available roof area of 18,825 m² can accommodate a 2.57 MWp photovoltaic system consisting of 4,720 bifacial modules and 25 inverter units. The system is capable of generating 3,809 MWh/year with a performance ratio of 83.86%. Economic evaluation shows that the project is feasible with a levelized cost of energy of 0.0987 USD/kWh and a net present value of 1,437,413 USD. In addition, the system has the potential to reduce carbon emissions by 50,299.7 tCO₂ during its operational lifetime. Therefore, the implementation of a rooftop solar power plant at the Amamapare coal field area is considered technically reliable, economically feasible, and environmentally beneficial.